How To Analyze Local Wisdom Contains In The Novel Series And Their Relation With The Author’s Society - Intama J. Polii (Universitas Muhammadiyah Ponorogo, 2019)
The literary is a type of original work by the author, as an impression of the life combined under the power of imagination and the creativity supported by the experience and life observation. The authors who live amidst society appreciate the intricate details in the secular society presence. This research discusses the method to analyze local wisdom contains in the novel series and their relationship with the author’s society. The sample novel series used in this study entitled Padang Bulan (PB) and Cinta Dalam Gelas (CDG) by Andrea Hirata, one of Indonesia’s novelist. The analysis combines the analytic-descriptive techniques, the content analysis, and the hermeneutics. The local wisdom and their contradiction can be traced and uncovered in light of the author's idea, which represents his society. It concludes that this method is easy to apply to other similar stories. It can help the readers understand the purpose of the story more accessible. The conflicting interest and the local wisdom can be compelling to be studied, while we can take the real lessons and the knowledge of another culture and their perspective to solve the issues of their life. Many of the analysis traces the explanation only and forget the true wisdom contains in every stories and matter